Dimensional comparisons in students' perceptions of the learning environment. (April 2016) - Arens, A. Katrin; Möller, Jens
Abstract: This study aims to add empirical evidence to the generalized internal/external frames of reference (GI/E) model, according to which students' social and dimensional achievement comparisons might not only be related to students' self-concepts but also to perceptions of the learning environment. In a sample of N  = 4926 German students, math and language achievements were measured along with two facets of students' perceptions of the learning environment, i.e., perceived instructional quality of math and language classes and perceived relations to math and language teachers. In the GI/E path model, achievement and perceptions of the learning environment were positively related within matching domains but negatively related or unrelated across non-matching domains. This pattern of relations indicates that social and dimensional achievement comparisons contribute to the formation of students' perceptions of the learning environment but the pattern of relations was stronger for math than for language achievement. Students' perceptions of instructional quality were more strongly related to achievement than perceptions of student–teacher relations. The findings were generalizable across same-aged elementary and secondary school students. The results are discussed regarding their implications for the proposed GI/E model and their importance for future research. Highlights: Assuming the GI/E model with social and dimensional achievement comparisons. Using two constructs of perceptions of the learning environment as outcomes. Positive within-domain relations between achievement and both constructs. Negative cross-domain relations between achievement and both constructs. Stronger GI/E pattern for instructional quality than for student–teacher relations.